Physical hazard control preventing injuries in the workplace - Spellman, Frank R. (Government Institutes, 2011)
"The book explains the proper controls for many types of physical hazards, including layout and building design, safeguarding of machinery, confined space entry, noise, radiation, ergonomics, electricity, thermal stressors, hand tools, woodworking, welding, machining, mobile equipment, materials handling, and workplace violence. Discussions of engineering controls, administrative controls (including safe work practices), and the use of personal protective equipment are supplemented with real-world examples and solutions. This book presents an up-to-date, practical guide focusing on a variety of physical hazards and controls. It is an informative text for students, a quick reference for safety professionals, a refresher for those preparing for certification, and a practical guide for those who need information on how to control physical hazards in their own places of work"--